Intake fraction estimates for on-road fine particulate matter (PM2.5) emissions: Exploring spatial variation of emissions and population distribution in Lisbon, Portugal. (October 2018) - Bastos, Joana; Milando, Chad; Freire, Fausto; Batterman, Stuart
Abstract: The intake fraction (iF) expresses population exposure resulting from pollutant emissions. City-wide iFs estimated using simple one-compartment models, which have been used in a number of previous studies, have significant uncertainties and do not capture the intra-urban variation in exposure that is important for estimating health effects associated with traffic-related air pollutants. We present a novel and efficient approach for developing spatially-resolved iF estimates using dispersion modeling for near-road exposures that accounts for the spatial and temporal variation in meteorology, emissions and the population living and working near major roads. Using the new approach, iF estimates are developed for emissions of traffic-related fine particulate matter (PM2.5 ) in Lisbon, Portugal, and compared to estimates from a one-compartment model. Both methods use local meteorological and population data and represent exposures for a total of 2.8 million people. The new method produces an overall iF value of 16.4 ppm for the Lisbon metropolitan area, over twice that of the one-compartment model (8.1 ppm). Most of the exposure (12.0 ppm) occurs for the subset of the population (1.0 million people) living or working within 500 m of highways and major arterials. The iF for the remainder of the population (1.8 million people) is only 4.3 ppm. The spatially-resolved iF estimate accounts for high concentration areas, which can be densely populated, and accounts for much or most of the exposure from traffic-related emissions. The new method is computationally efficient and can improve estimates of exposure and health impacts occurring in urban areas, leading to more effective urban and transportation planning decisions to mitigate impacts. Highlights: iF estimates specifically for traffic-related air pollution are estimated. Intra-urban variation is accounted for by combining dispersion modeling and GIS. An iF of 16.4 ppm was estimated for primary PM2.5 in the Lisbon metropolitan area. About 74% of the intake (12.0 ppm) occurred in the near-road (within 500 m). The method is computationally efficient compared to conventional dispersion models.